(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of sleep quality among parents caring for children receiving treatment at the Immunology - Allergy - Rheumatology Department, Vietnam National Children’s Hospital in 2024. Method: Cross-sectional descriptive study on 365 parents of pediatric patients, assessing sleep quality based on the PSQI toolkit. Results: The average PSQI score was 6.0 ± 3.2, the lowest was 0 and the highest was 16 points. 49.3% of parents had poor sleep quality (PSQI score > 5). There was a correlation between sleep quality and factors: the caregiver was the mother, sleep was affected by light, and there was pressure on treatment costs. Conclusion: About half of parents caring for pediatric patients had sleep quality. Financial support should be increased for children with difficult circumstances. Parents can reduce the impact of light on sleep by using eye masks.